Kontribusi Panjang Tungkai dan Power Otot Tungkai Terhadap Tendangan Ushiro Geri pada Atlet Karate Putra - Holly Viet Kogoya, Yeremi (Jurnal Muara Olahraga, 2025)
This study aims to determine the contribution of leg length and leg muscle power to the ushiro geri kick performance in male karate athletes. This research employs a quantitative analysis approach, with variables X1 and X2 representing leg length and leg muscle power, respectively, and Y representing the kick performance. The study population consists of all 22 male karate athletes from INKAI Driyorejo Gresik. The research instruments include a measuring tape for leg length, a vertical jump test for leg muscle power, and the Kinovea program for kick performance assessment. Data were analyzed using descriptive quantitative analysis, normality tests, and regression analysis at a significance level of α = 0.05, with the assistance of SPSS version 21.The results of the study indicate that: 1) Leg length has a significant contribution of 48.8% to the ushiro geri kick performance. 2) Leg muscle power has a significant contribution of 19.67% to the ushiro geri kick performance. 3) The combined contribution of leg length and leg muscle power to the ushiro geri kick performance is 67.97%.